Identifikasi Service Blueprint di Desa Wisata Kebontunggul (Lembah Mbencirang), Kecamatan Gondang, Kabupaten Mojokerto - Agung Yoga Asmoro; M. Nilzam Aly; Handika Fikri Pratama (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This study aims to comprehend the actual conditions of business processes and to identify service blueprints in the Kebon Tunggul Tourism Village "Lembah Mbencirang" by analyzing their business activities and service flows to visitors. This research is community-based research (CBR) conducted using the Participatory Action Research (PAR) approach. It resulted in the findings that there were various internal problems related to management during 2017-2020, especially related to the accountability and transparency of budget management in addition to more fundamental issues regarding tourist attraction management, such as the absence of an organizational structure, no clear division of staff duties, and the nonappearance of a standardized service flow. We concluded that basically, the business processes in the Lembah Mbencirang can be grouped into two, the first is the package tour services, and the second is the general visitors’ services. As a tourism product which is essentially a service product, service blueprint is very significant as an effort to understand the service experience from the perspective of the customer, which in this context was not previously owned by the manager. The service blueprint generated from this study can identify the existence of various service processes so that all staff can cognize the context and conditions of their duties in a more holistic customer service perspective.